Energy Security and Energy Transition to Achieve Carbon Neutrality - Rabbi, Mohammad Fazle; Popp, József; Máté, Domicián; Kovács, Sándor (Energies (Basel), 2022)
Successful energy transitions, also referred to as leapfrog development, present enormous prospects for EU nations to become carbon neutral by shifting from fossil fuels to renewable energy sources. Along with climate change, EU countries must address energy security and dependency issues, exacerbated by factors such as the COVID-19 pandemic, rising energy costs, conflicts between Russia and Ukraine, and political instability. Diversifying energy sources, generating renewable energy, increasing energy efficiency, preventing energy waste, and educating the public about environmental issues are proposed as several strategies. The study draws the conclusion that central European countries may transition to a clean energy economy and become carbon neutral on economic and strategic levels by locating alternative clean energy supply sources, reducing energy use, and producing renewable energy. According to the study, the EU energy industry can be decarbonised and attain energy security using three basic strategies, such as supply diversification, energy savings, and quicker adoption of renewable energy to replace fossil fuels. The energy transformation industry still needs to improve energy efficiency, incorporate a circular and sustainable bioeconomy, and support renewable energies, including solar, wind, hydropower, nuclear, and hydrogen.